'Tubeless' nephrectomy: Routine omission of indwelling catheters and abdominal drains and impact on patient outcomes. (March 2017) - Hughes, Paul; Chandra, Lizzie; Lunawat, Rahul; Cartledge, Jon
Objective: Continued refinements to the enhanced recovery after surgery (ERAS) protocols can help improve patient care. This study details the experience and outcomes of a single surgeon's practice over a two-year period for all laparoscopic renal surgery where omitting abdominal drains and indwelling catheters, 'tubeless nephrectomy', was the default. Methodology: A total of 178 consecutive unselected patients underwent laparoscopic renal surgery during a 22-month period. This included laparoscopic radical, partial, live donor and benign nephrectomy cases. Demographic details and data on length of stay, complications and the need for catheterisation post-operatively and use of abdominal drains were collected prospectively. Results: Of the patient group, 142 (80%) underwent entirely 'tubeless' procedures. Catheterisation (indwelling catheter (IDC) or clean intermittent catheterisation (CIC)) was required in 23 (13%) patients, 11 (6%) had a drain placed at operation and two had both. The median length of stay for tubeless procedures was one day (interquartile range (IQR) 1–2, range 1–22 days). This compared to a median length of stay of three days (IQR 1–6) for those with a catheter and two days (IQR 1.5–4.5) for those with a drain post-operatively. The difference between the median length of stay for tubeless and non-tubeless procedures was statistically significant ( p =0.001). The difference in frequency of complications between the tubeless group and those who received a drain or catheter was also significant ( p =0.003). Conclusions: This change in clinical practice is safe, effective and easy to implement. When incorporated into laparoscopic nephrectomy ERAS protocols, 'tubeless' surgery can have a significant benefit on length of stay and patient outcomes, without a detrimental impact on complication rates.